2019
DOI: 10.1097/md.0000000000018433
|View full text |Cite
|
Sign up to set email alerts
|

The management of Salter-Harris type II fracture with associated posterior sternoclavicular joint displacement using a locking compression plate

Abstract: Rationale: Posterior sternoclavicular joint dislocations (PSCJDs) are particularly rare injuries, accounting for 3% to 5% of sternoclavicular joint dislocations. With very few cases reported in the literature, these injuries are often misdiagnosed and imaging is not always clear, thus making physicians often unaware of them. The present case report aims to investigate a rare case involving a clavicular Salter-Harris II fracture with associated posterior displacement of the diaphysis, a term coined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Regardless of the surgical methods performed, important thoracic structures which exist behind the sternoclavicular joint, such as the trachea, esophagus, brachiocephalic vein, brachiocephalic artery, and brachial plexus, were protected from accidental injury caused by surgical treatment, especially on the sternal manubrium [ 3 , 14 , 15 ]. As a classical surgical method, LPs have been used for the reduction and fixation of the sternoclavicular joint [ 16 , 17 ]. Additionally, we also have reported the safety and efficacy of using an AJHP for the treatment of anterior sternoclavicular joint dislocation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the surgical methods performed, important thoracic structures which exist behind the sternoclavicular joint, such as the trachea, esophagus, brachiocephalic vein, brachiocephalic artery, and brachial plexus, were protected from accidental injury caused by surgical treatment, especially on the sternal manubrium [ 3 , 14 , 15 ]. As a classical surgical method, LPs have been used for the reduction and fixation of the sternoclavicular joint [ 16 , 17 ]. Additionally, we also have reported the safety and efficacy of using an AJHP for the treatment of anterior sternoclavicular joint dislocation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Important thoracic structures, such as the trachea, esophagus, brachiocephalic vein, brachiocephalic artery, and brachial plexus, exist behind the sternoclavicular joint, and surgical treatment may be required to prevent accidental injury, especially on the sternal manubrium [3,14,15]. As a classical surgical method, LPs have been used for the reduction and xation of the sternoclavicular joint [16,17]. We have reported the safety and e cacy of using an AJHP for the treatment of anterior sternoclavicular joint dislocation [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many different surgical techniques described in the literature; however, there is no widely accepted ideal surgical method. 1 , 2 , 3 , 5 , 14 , 15 A biomechanical cadaveric study done by Spencer and Kuhn 10 demonstrated that a figure-of-eight reconstruction restores superior joint stability compared with other techniques, especially in the posterior direction. Kendal et al 4 performed a systematic review of surgical management of traumatic posterior SCJDs in both adult and adolescent patient populations and found 45 different surgical techniques.…”
mentioning
confidence: 99%